2016
DOI: 10.1113/ep085837
|View full text |Cite
|
Sign up to set email alerts
|

Activation of autonomic thermoeffectors preceding the decision to behaviourally thermoregulate in resting humans

Abstract: New Findings r What is the central question of this study?Do increases in metabolic heat production and sweat rate precede the initiation of thermoregulatory behaviour in resting humans exposed to cool and warm environments? r What is the main finding and its importance?Thermoregulatory behaviour at rest in cool and warm environments is preceded by changes in vasomotor tone in glabrous and non-glabrous skin, but not by acute increases in metabolic heat production or sweat rate. These findings suggest that swea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 52 publications
(125 reference statements)
6
23
0
Order By: Relevance
“…Schlader and colleagues have been at the forefront of addressing this important gap in the literature and, in the current issue of Experimental Physiology, expand on their previous work by addressing the question of whether changes in metabolic heat production and sweating precede thermal behaviour (Schlader et al 2009(Schlader et al , 2013(Schlader et al , 2016a. Using a novel experimental design, in which participants were free to move between cool and warm rooms, Schlader et al (2016a) found that initiation of thermal behaviour precedes any changes in metabolic heat production when going from a cool to a warm room as well as changes in sweating when going from a warm to a cool room.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Schlader and colleagues have been at the forefront of addressing this important gap in the literature and, in the current issue of Experimental Physiology, expand on their previous work by addressing the question of whether changes in metabolic heat production and sweating precede thermal behaviour (Schlader et al 2009(Schlader et al , 2013(Schlader et al , 2016a. Using a novel experimental design, in which participants were free to move between cool and warm rooms, Schlader et al (2016a) found that initiation of thermal behaviour precedes any changes in metabolic heat production when going from a cool to a warm room as well as changes in sweating when going from a warm to a cool room.…”
mentioning
confidence: 99%
“…Conversely, initiation of thermal behaviour appeared to coincide with changes in cutaneous vasomotor tone such that there was substantial cutaneous vasoconstriction when moving from a cool to a warm room and maximal withdrawal of vasoconstrictor tone when moving from warm to cool (and perhaps engagement of the active vasodilator system; Schlader et al 2016a). Inasmuch as changes in skin blood flow can affect skin temperature, the findings of Schlader et al (2016a) appear to support the notion that changes in skin temperature are the primary determinants of thermal behaviour (Cabanac et al 1972;Schlader et al 2013). If, as proposed above, we accept the concept that thermal behaviour is a mechanism to maintain thermal homeostasis and, perhaps, to minimize our reliance on physiology, these findings make sense.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified that the initiation of thermal behavior temporally precedes the initiation of sweating in the heat and changes in metabolism in the cold [3]. However, thermal behavior is consistently preceded by changes in skin blood flow [3].…”
mentioning
confidence: 99%
“…When given the opportunity to behaviorally thermoregulate, the initiation of thermal behavior is mediated by changes in skin temperature, largely preventing changes in core temperature [3]. We have previously identified that the initiation of thermal behavior temporally precedes the initiation of sweating in the heat and changes in metabolism in the cold [3].…”
mentioning
confidence: 99%